The unique contribution of a local response group in the field investigation and management of a trichinellosis outbreak in Nunavik (Québec, Canada) - Lemire, Mélanie; Proulx, Jean-François; Lévesque, Benoît; Simard, Manon; Iqaluk, Martha; Ducrocq, Julie; Elijassiapik, Lisa; Ningiuk, Etok; Perkins, Pamela (Canadian Public Health Association, 2020)
Setting : Consumption of raw game meats is important for Inuit health and well-being but may sometimes increase risk of exposure to parasites. In Nunavik, following trichinellosis outbreaks in the 1980s caused by raw walrus consumption, a diagnostic test was developed for the region and offered to all Inuit communities by 1997. Despite this prevention program, an important trichinellosis outbreak occurred in 2013, affecting 18 inhabitants of Inukjuak. Intervention : Because the classical outbreak investigation did not rapidly converge toward a common food source or specific event, a local response group, composed of four community members appointed by the Municipal Council as well as the regional public health physician, nurse and wildlife parasitologist, was created. Their objective was to investigate potential sources of infection related to the outbreak, hence the investigation of the types of meats consumed, the movement of meats between and within the community, and the local practices of processing game meat. Outcomes : Though the source of infection was not fully confirmed, this local investigation identified the distribution of transformed polar bear meat as the most probable source of infection. The creation of this unique, intersectoral and intercultural local response group fostered the use of local knowledge to better understand aspects of the modern food system, and is one of the most innovative outcomes of this investigation. Implications : Integrating multiple ways of knowing was critical for the management of this important public health issue and contributed to community members’ mobilization and empowerment with respect to local food safety issues. Contexte : La consommation de viandes de gibier crues est importante pour la santé et le bien-être des Inuits, mais elle peut parfois augmenter leur risque d'exposition à certains parasites. Au Nunavik, après quelques éclosions de trichinellose causées par la consommation de viande de morse crue dans les années 1980, un test diagnostic a été ...